ANALISIS QUALITY OF SERVICE (QoS) LIVE STREAMING WIRELESS IP CAMERA XONZ BERBASIS SMARTPHONE ANDROID - Larosa, Fati Gratianus Nafiri; Laia, Ofelius (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2019)
Quality of Service (QoS) on Live Streaming has the main parameters, namely bandwidth, jitter, loss and delay, which are measured on the implementation of Wireless IP Camera based on Android Smartphone. The test tools used iperf and ping software, to capture data packets. The network design in this study uses Xonz Wireless IP Camera, wifi router, Server/Laptop and Android Smartphone to monitor or access the services provided. Surveillance/reconnaissance or surveillance by accessing live streaming can be done from anywhere as long as there is still an intranet network. wifi router provides DHCP service, Server/Laptop provides a Virtual Machine using MS Windows Server 2003 Operating System. Web Server is not installed on Real Machine but on Virtual Machine. The smartphone used has the Android Operating System version 4.4.2. IP Camera Xonz model XZ-12Z-HR/W has one major drawback that it can only be accessed via Internet Explorer Browser which can only run on MS Windows Operating System. Some applications that are already available on Google Play and installed on Android Smartphones cannot detect the Wireless IP Camera. The outcome or impact of this research is the creation of a simple Live Streaming application that can be accessed by all browsers on all platforms including Android Smartphones. Measurements were made using iperf and ping. The results showed that the Xonz IP Camera can still be used for mobile room monitoring as far as a maximum of about 20 m from the wifi router and still meets the standard QoS values ​​set by TIPHON and ITU-T G.114.